2018
DOI: 10.1055/a-0573-2419
|View full text |Cite
|
Sign up to set email alerts
|

Anwendung der hyperthermen intrathorakalen Chemotherapie (HITHOC) in Deutschland

Abstract: HITHOC is performed in at least 17 departments of thoracic surgery in Germany, and is widely standardised with protective measures and a low rate of complications. The aims of the HITHOC are improvement in local tumor control in pleural malignancies combined with prolonged overall survival and better quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…EPP itself can lead to severe medical and surgical complications and requires multidisciplinary expertise for both prevention and management [14]. In a meta-analysis of 21 studies for pleural mesothelioma, the authors found that while surgery may cause complications like bronchopleural fistula, diaphragm rupture, or laryngeal nerve dysfunction, HITHOC itself did not cause such adverse effects [15]. A review of HITHOC performed at German thoracic surgery centers also found a low rate of major complications [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPP itself can lead to severe medical and surgical complications and requires multidisciplinary expertise for both prevention and management [14]. In a meta-analysis of 21 studies for pleural mesothelioma, the authors found that while surgery may cause complications like bronchopleural fistula, diaphragm rupture, or laryngeal nerve dysfunction, HITHOC itself did not cause such adverse effects [15]. A review of HITHOC performed at German thoracic surgery centers also found a low rate of major complications [16].…”
Section: Discussionmentioning
confidence: 99%
“…Looking at each of the diseases individually, the median survival in pleural mesothelioma is dismal. With multimodality treatment comprising of surgery with intrathoracic and systemic chemotherapy with or without radiotherapy, the median survival is still only 15-18 months and the median DFS under 12 months [15]. The therapy itself is intense, and many patients may not be able to withstand this aggressive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperthermic intrathoracic chemotherapy (HITOC) is an innovative, additive treatment for selected patients with primary or secondary malignant pleural tumors. In Germany, about 350 of these procedures have been performed in 10 years by 17 specialized clinics, and the number is increasing (Ried et al 2018). Over a period of 60 min, the thoracic cavity is perfused with a heated solution to improve local tumor control after surgical cytoreduction .…”
Section: Introductionmentioning
confidence: 99%
“…These results urge caution, but dermal contact can be prevented by taking the appropriate safety measures (Landeck et al 2015). To prevent the exposure of the operating room (OR) personnel, specific safety regulations must be applied (safety instruction, gloves compatible with cytostatic drugs, protective surgical gowns, safety glasses, dedicated containers for disposal of cytostatic agents) (Ried et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…= erweiterte Pleurektomie/Dekortikation, EPP = extrapleurale Pneumonektomie, P/D = Pleurektomie/Dekortikation, SD = Standardabweichung, VATS = videoassistierte Thorakoskopie rapie (HITOC) durchgeführt, dies wurde von insgesamt 9 Kliniken dokumentiert (▶ Tab. 2)[7].Sekundäre PleurakarzinoseBei 317 (61,4 %) Patienten des Registers wurde eine thoraxchirurgische Behandlung aufgrund einer sekundären Pleurakarzinose durchgeführt. Insbesondere Bronchial-(33,5 %; n = 107) oder Mammakarzinome (27,9 %; n = 89) wurden häufig als Primarius genannt, sodass allein diese beiden Entitäten 2 2 ⁄3 3 der Primärtumoren ausmachten.…”
unclassified